Pengaruh Variabel Moneter terhadap Variabel Internal Bank Konvensional di Indonesia - Ali Akbar (Ekonomis: Journal of Economics and Business, 2019)
This research is to know the influence of monetary variables ((interest rate, exchange rate and amount of money supply) on the internal variables of conventional banks (amount of credit and operational expense than operating income (BOPO)). The population in this research is the whole of conventional banks in Indonesia year of 2010-2017. The sampel is the conventional banks by as much as 14 banks, with time series data. The method used is the analysis of partial least square (PLS). The results showed that monetary variables ((interest rate, exchange rate and amount of money supply) have a positive and significant influence on the internal variables of conventional banks (amount of credit and BOPO), where excange rate (rupiah on dollar AS) is the most influential variable on amount of credit and BOPO of conventional banks compared to the interest rate and amount of money supply variable.